2019
DOI: 10.1136/bmjopen-2018-025825
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia-related complications and side-effects in TAVI: a retrospective study in Germany

Abstract: ObjectivesThis study was performed to analyse anaesthesia-related complications and side effects in patients undergoing transcatheter aortic valve implantation (TAVI) under general anaesthesia.DesignRetrospective study.SettingThe study was performed as a single-centre study in a hospital of tertiary care in Germany.ParticipantsAll 853 patients, who underwent TAVI at the Universitätsklinikum Regensburg between January 2009 and July 2015, were included. 52.5% were female patients.Primary and secondary outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Tissue trauma, pain perception, and psychological emotion will activate hypothalamus-pituitary-adrenal axis and sympathetic nervous system, triggering stress response, thereby reducing the perioperative stress response of patients, which is conducive to patients' recovery and can reduce the occurrence of potential complications [ 18 , 19 ]. Evidence has shown that appropriate depth of anesthesia can reduce the stress response of patients undergoing surgery and improve the hemodynamic stability of patients [ 20 , 21 ]. The results of this study revealed that at T1 and T2, the MAP value was higher and the CVP value was lower in NT group compared with group C, and higher CRP, IL-6, and Cor were determined in NT group at T1-T3.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue trauma, pain perception, and psychological emotion will activate hypothalamus-pituitary-adrenal axis and sympathetic nervous system, triggering stress response, thereby reducing the perioperative stress response of patients, which is conducive to patients' recovery and can reduce the occurrence of potential complications [ 18 , 19 ]. Evidence has shown that appropriate depth of anesthesia can reduce the stress response of patients undergoing surgery and improve the hemodynamic stability of patients [ 20 , 21 ]. The results of this study revealed that at T1 and T2, the MAP value was higher and the CVP value was lower in NT group compared with group C, and higher CRP, IL-6, and Cor were determined in NT group at T1-T3.…”
Section: Discussionmentioning
confidence: 99%
“…The valve and anesthesia comparisons were published separately in two journals, 12,13 and both were included as a complete study in the meta‐analysis. The majority of the included studies were observational (33 prospective studies, 14–46 28 retrospective studies, 47–74 and 4 studies with unknown nature 75–78 ), with only four RCTs 12,13,79–81 . The number of included patients varied widely, ranging from 25 to 170,521 per study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the incidence of POD was rather low. The presumed number of participants was calculated based on the incidence of POD previously described in our TAVR population [ 28 ].…”
Section: Discussionmentioning
confidence: 99%